PERANCANGAN SISTEM INFORMASI ANALISIS MEDIK MENGGUNAKAN LOGIKA FUZZY SUGENO BERBASIS DATA REKAM MEDIK PADA PENYAKIT HIPERTENSI - Nadhira Trisa Pradipta; Fauziah; Ucuk Darusalam (Jurnal Ilmiah Informatika, 2017)
Number of patients with hypertension have increased from year to year. This is due to an unhealthy lifestyle, excessive stress and so forth. Patiens with hypertension are often unaware of the dangers that can be caused by disease. The medical diagnosis of hypertension is made when obtained blood pressure is obtained more than 140/90 mmHg. In this study, created a system of enforcement of hypertension using sugeno fuzzy logic. This application uses the parameters of age, body mass index, blod pressure(systole and diastole), family history (genetics), diabetes mellitus. From testing the fuzzy logic that has been done, can be obtained on the calculation of 60 patients who did not suffer from hypertension (normal) as much 3 people, who suffer from prehypertension as much 17 people, who suffer from hypertension grade 1 as much 25 people and who suffer from hypertension degrees 2 as much 15 people. With an average accuracy test rate 99.999989% for patients who did not suffer from hypertension, 99.999985% for patients who suffer from prehypertension, 100% who suffer from hypertension grade 1 and 99.999946% who suffer from hypertension degrees 2. With an average the level of error 0.00333% for patients who did not suffer from hypertension, 0.00471% for patients who suffer from prehypertension, 0% who suffer from hypertension grade 1 and 0.00733% who suffer from hypertension degrees 2. From the application made can provide clear, accurate information about hypertension disease.